Body Mass Index (BMI) and Glucose Intolerance during Pregnancy in White European Women - Farah, Nadine (Avicenna Research Institute, 2012)
BACKGROUND: The risk of gestational diabetes mellitus (GDM) in accordance to Body Mass Index (BMI) is often based on studies where the calculation of BMI is frequently self-reported and is usually unreliable. We evaluated the risk of an abnormal oral glucose tolerance test (OGTT) in a population where BMI was measured and selective screening for GDM was practiced. METHODS: We carried out a prospective observational study where 1935 white European women with a singleton pregnancy were recruited. In the first trimester maternal height and weight were measured digitally. Statistical analysis was performed using SPSS version 15.0. BMI centiles were calculated from the study population. A Chi-square test was used to test the differences in categorical variables between the groups. A p-value <0.05 was considered significant. RESULTS: In 1935 women, 547 OGTTs were performed and 70 of these were abnormal. The prevalence of an abnormal OGTT was higher in women with Class 2 and 3 obesity compared to women with Class 1 obesity (23.3% vs. 10.1%, respectively; p= 0.008). The frequency of an abnormal OGTT was higher in women with a BMI ≥90th centile (≥33.1 kg/m (2)) compared to women with a BMI between the 80th and 90th centiles (≥29.3 and <33.1 kg/mm (2)), (21.5% vs 8.1% respectively; p = 0.005). CONCLUSION: When BMI is measured, we recommend to increase the cut-off point for selective screening of GDM to ≥33.0 kg/m (2). This may decrease unnecessary obstetric interventions and healthcare costs.